MENINGKATKAN MANAJEMEN PRESENSI KARYAWAN DENGAN OPTIMALISASI APLIKASI SAP PADA PT XYZ - Citra Syifa Nailuvar; Agung Nugroho (Jurnal Administrasi Perkantoran, Bisnis, dan Manajemen Daksa, 2023)
The purpose of this journal is to present information regarding the importance of optimizing applications and digitalization knowledge for a secretary. A secretary plays an administrative role, and one of their responsibilities is to act as an effective communication bridge within a company. However, with the advancement of globalization, the usual administrative tasks performed by a secretary can be replaced by technology. To address this issue, it is advisable for a secretary to become an initiator in utilizing technology. Based on the background mentioned above, the author will explain: 1) The implementation of secretarial tasks at PT XYZ.2) Comparing the learned theoretical foundations with the findings 3) The role of a secretary in the field of technology in the present era 4) Recommendations for the applications used by PT XYZ to enhance attendance management. The outcome of this paper yields the following results: 1) The reasons why digital skills are necessary for a secretary 2) Ways to improve attendance management at PT XYZ 3) Suggestions to produce a secretary who possesses high self-confidence, critical thinking skills, self-improvement capabilities, multitasking abilities, the ability to enhance the credibility of the educational institution and the company, as well as systematic and structured thinking.